Effect of coupling agent on mechanical, thermal and water absorption behavior of polypropylene / coconut coir composites - Emhemed, Jbril Ibrahim Ahmed (School of Materials Engineering, Universiti Malaysia Perlis, 2010)
i- To study the effect of coupling agent on mechanical properties (tensile and flexural) of polypropylene / coconut coir composites. ii- To investigate the effect of different percentages of fiber onto composites. iii- To study the effect of coupling agent on the composites by thermal and water absorption.